The evolution and cross-section of the day-of-the-week effect - Shlomo Zilca (Financial Innovation, 2017)
We study the day-of-the-week effect across size deciles and in three 18-year subperiods. The results show a decline in the magnitude of the day-of-the-week effect, but the effect did not vanish. We find that the decline in the magnitude of the effect is larger in the larger market capitalization deciles. We also find substantial evidence that the day-of-the-week effect is characterized by a pattern of monotonically improving returns during the week, but the pattern is interrupted as market capitalization increases. The behavioral explanation for the day-of-the-week effect, based on monotonically improving mood throughout the week, is therefore a stronger candidate in smaller-market capitalization deciles.
Keywords: 650; Day-of-the-week effect; Monday effect; Behavioral finance